EFEKTIVITAS TEKNIK OKULASI DAN APLIKASI ZAT PENGATUR TUMBUH TERHADAP KEBERHASILAN DAN PERTUMBUHAN AWAL JERUK SIAM PONTIANAK (Citrus nobilis Var. microcarpa) - Keli, Maria Oktaviana; Indawan, Edyson; Hapsari, Ricky Indri; Sumiati, Astri (BUANA SAINS, 2025)
The success of budding is influenced by various factors, including the technique employed and the application of Plant Growth Regulators (PGRs). This study aimed to determine the most effective budding technique and type of PGR to enhance the success rate and initial growth of Siam Pontianak citrus (Citrus nobilisÂ var.Â microcarpa) seedlings. The research was conducted from March to May 2025 in Batu City, East Java, using a Factorial Randomized Complete Block Design (RCBD). The first factor was the budding technique: patch budding, T-budding, and chip budding. The second factor was the type of PGR: control (water), young coconut water (500 ml/L), and Atonik (1 ml/L). The analysis of variance (ANOVA) revealed no significant interaction between the two factors. However, as independent factors, the chip budding technique resulted in the highest success percentage and number of shoots (P0.05). The application of coconut water led to the fastest sprout emergence, as well as the greatest shoot height and number of leaves compared to the other PGR treatments and the control. It is concluded that chip budding is the superior method for graft union success, while coconut water is the most effective PGR for promoting the initial vegetative growth of the budded seedling.